Conflict and the Social Contract - Helmut Bester; Karl Wärneryd (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2006)
We consider social contracts for resolving conflicts between two agents who are uncertain about each other's fighting potential. Applications include international conflict, litigation, and elections. Even though only a peaceful agreement avoids a loss of resources, if this loss is small enough, then any contract must assign a positive probability of conflict. We show how the likelihood of conflict outbreak depends on the distribution of power between the agents and their information about each other.
urn:nbn:de:bvb:19-epub-13457-7
Keywords: 330; conflict; social contracts; asymmetric information